2018
DOI: 10.1590/1414-431x20187575
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and eating behavior in depot medroxyprogesterone acetate users: a systematic review

Abstract: Because of weight gain, women often discontinue hormonal contraception, especially depot medroxyprogesterone acetate (DMPA). Our objective was to conduct a systematic review of studies describing dietary intake or eating behavior in DMPA users to understand whether the use of DMPA is associated with changes in dietary habits and behaviors leading to weight gain. We searched the PubMed, POPLINE, CENTRAL Cochrane, Web of Science, and EMBASE databases for reports published in English between 1980 and 2017 examini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Individuals who use hormonal contraceptives will generally experience an improved diet. This leads to an increase in the amount of food intake, resulting in an increased risk of weight gain (Silva et al, 2018). In addition, at the beginning of use, there can be temporary fluid retention, resulting in a temporary increase in body weight (De Leo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who use hormonal contraceptives will generally experience an improved diet. This leads to an increase in the amount of food intake, resulting in an increased risk of weight gain (Silva et al, 2018). In addition, at the beginning of use, there can be temporary fluid retention, resulting in a temporary increase in body weight (De Leo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The longer the use of hormonal contraceptives, the longer the increase in appetite occurs. This situation causes the increase in food intake also lasts a long time, resulting in an accumulative increase in body weight (De Leo et al, 2016;Silva et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, as the data in the current study was collected from routine gynecological DMPA visits physical activity and nutritional status data was not collected and serves as a study limitation. A systemic review by Silva et al examining dietary intake and eating behavior among DMPA users was not able to determine if DMPA contributes to changes in eating behavior which could possibly serve as an explanation for weight gain by its users [19]. Another study, though small with only 43 patients, reported that despite a decrease in appetite black adolescents gained more weight and body fat on DMPA compared to white adolescents who were on DMPA for the same amount of time, suggesting racial differences in weight gain and body composition while on DMPA [12].…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…Weight loss/gained was calculated (weight at study end -weight at study beginning). The gray box indicates women who were adolescents (age[16][17][18][19] at the beginning of the study. The color of the dot corresponds to the BMI category.…”
mentioning
confidence: 99%